Malignancies in human immunodeficiency virus infected patients in India: Initial experience in the HAART era - Sharma, Surendra K. (Indian J Med Res, 2015)
BACKGROUND & OBJECTIVES: Limited data are available on malignancies in human immunodeficiency virus (HIV)-infected patients from India. We undertook this study to assess the frequency and spectrum of malignancies in HIV-infected adult patients during the first eight years of highly active antiretroviral therapy (HAART) rollout under the National ART Programme at a tertiary care centre in New Delhi, India. METHODS: Retrospective analysis of records of patients registered at the ART clinic between May 2005 and December 2013 was done. RESULTS: The study included 2598 HIV-infected adult patients with 8315 person-years of follow up. Malignancies were diagnosed in 26 patients with a rate of 3.1 (IQR 2.1-4.5) cases per 1000 person-years. The median age for those diagnosed with malignancy was 45 (IQR 36-54) yr, which was significantly (P<0.01) higher compared with those not developing malignancies 35 (IQR 30-40) yr. The median baseline CD4+ T-cell count in patients with malignancy was 135 (IQR 68-269) cells/µl compared to 164 (IQR 86-243) cells/µl in those without malignancies. AIDS-defining cancers (ADCs) were seen in 19 (73%) patients, while non-AIDS-defining cancers (NADCs) were observed in seven (27%) patients. Malignancies diagnosed included non-Hodgkin's lymphoma (16), carcinoma cervix (3), Hodgkin's lymphoma (2), carcinoma lung (2), hepatocellular carcinoma (1), and urinary bladder carcinoma (1). One patient had primary central nervous system lymphoma. There was no case of Kaposi's sarcoma. INTERPRETATION & CONCLUSIONS: Malignancies in HIV-infected adult patients were infrequent in patients attending the clinic. Majority of the patients presented with advanced immunosuppression and the ADCs, NHL in particular, were the commonest malignancies.